IMPLEMENTATION OF GUIDANCE PROGRAMS FOR PRISONERS IN THE CLASS I DETENTION CENTER LABUHAN DELI - Dia Nita Laurellia br Tarigan; Siti Hazzah Nur R (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
The prisoner guidance programs are part of the correctional system, which is carried out in the penitentiary (Lapas). The problem that occurs is that most of the conditions in Lapas have exceeded capacity, so the guidance programs must also be carried out at the Detention Center (Rutan). This increased Rutan's function and caused Rutan to face a number of challenges. The purpose of this study is to describe the implementation of guidance programs for prisoners at the Labuhan Detention Centerlem that occurs is that most of the conditions in Lapas have exceeded capacity, so the guidance programs must also be carried out at the Detention Center (Rutan). This increased Rutan's function and caused Rutan to face a number of challenges. The purpose of this study is to describe the implementation of guidance programs for prisoners at the Labuhan Detention Center. This study uses a qualitative research method with a phenomenological approach. The obtained data were analyzed using the implementation theory put forward by Charles O. Jones, including organization, interpretation, and application. Through this research, it is known that the guidance programs for prisoners in Class I Detention Center Labuhan Deli are running quite well. It can be seen in the existence of an organizational structure and a clear division of tasks, adequate resources, work procedures, activity schedules, and good communication with other organizations. However, the socialization carried out by the detention center has not been optimal, and the marketing of products made by prisoners is still limited.